THEOSOPHICAL SOCIETY IN GLOBALIZATION PERSPECTIVE - Fardana Khirzul Haq (Jurnal Al-Dustur, 2020)
Modernistic globalization with empirical and rational methods has given its significant advancement to Western society. The advancement, however, eroded the spiritual values, especially Christianity, that for almost ten centuries championed the Europeans minds. Spiritualism or religions is regarded as ancient and have no value in the development of society. Blavatsky and Olcott felt that the rapid growth of modernistic globalization has to be equaled by spiritualism. Therefore, they founded an organization with goals to reestablish spiritual and traditional values that have been long lost from Western society. In order to challenge the modernistic globalization, Theosophical Society used spiritualistic globalization. The organization is quite successful and gains lots of followers from renowned people. Olcott, the first president, is an experienced media person. Newspapers and magazines are the two main components that brought the organization to its fame.